Socioeconomic, Behavioral, and Environmental Predictors of Tuberculosis Treatment Duration: A Multivariate Analysis in Urban Indonesia - Wahyu Indah Dewi Aurora; Maharani; Tia Wida Ekaputri; Armaidi Darmawan; Erny Kusdiyah; Andika Sulistiawan (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Tuberculosis (TB) in Indonesia currently ranks second globally in TB incidence. The disease causes an estimated 125,000 deaths annually. Prolonged treatment duration increases the risk of treatment interruption, drug resistance, and financial burden on patients. This study aimed to analyze the socioeconomic, behavioral, and environmental predictors associated with TB treatment duration. Methods: A cross-sectional design was applied across primary health centers in Jambi City, Indonesia. The study population included individuals at risk of TB, and 297 pulmonary TB patients were recruited using purposive sampling. Independent variables included socioeconomic status, smoking behavior, TB-related knowledge, patient attitude toward treatment, and housing density. Chi-square tests were used for bivariate analysis, and multivariate logistic regression was performed to identify dominant predictors of prolonged treatment duration. Results and Discussion: A total of 40.1% of patients experienced prolonged treatment (> 6 months). Bivariate analysis showed significant associations between treatment duration and socioeconomic status (p < 0.001), smoking behavior (p = 0.018), TB knowledge (p = 0.004), treatment attitude (p = 0.001), and housing density (p = 0.009). Multivariate analysis identified low socioeconomic status (AOR = 2.15, 95% CI: 1.34–3.47) and negative treatment attitude (AOR = 1.82, 95% CI: 1.19–2.79) as the strongest predictors of prolonged treatment duration. Conclusion: Patients with limited financial resources may face structural barriers to treatment completion, including transportation costs, unstable income, and competing daily priorities. These findings have important implications for Indonesia’s TB program and align with the WHO End TB Strategy, which emphasizes addressing social determinants of health.